Walking Beyond Our Borders With Frontline Health Workers in Guatemala. Issue 6 (December 2013) - Walker, Raquel
Abstract In many developing countries, access to health care can be out of reach for many women and newborns. Trained frontline health workers serve as the first point of contact for medical care in many of these areas, and their efforts can prevent illness and death from conditions such as malaria, pneumonia and diarrhea. Their work is especially vital to reducing maternal and newborn morbidity and mortality. Due to the global shortage of health workers, nurses and organizations need to collectively advocate for the support and training of frontline health workers.